The Construction and Comprehensive Prognostic Analysis of the LncRNA-Associated Competitive Endogenous RNAs Network in Colorectal Cancer - Li, Wei; Yu, Weifang; Jiang, Xia; Gao, Xian; Wang, Guiqi; Jin, Xiaojing; Zhao, Zengren; Liu, Yuegeng (Frontiers in Genetics, 2020)
Competitive endogenous RNAs (ceRNAs) are a newly proposed RNA interaction mechanism that has been associated with the tumorigenesis, metastasis, diagnosis and predicting survival of various cancers. In this study, we constructed a ceRNA network in colorectal cancer (CRC). Then, we sought to develop and validate a composite clinicopathologic-genomic nomogram using TCGA database. To construct the ceRNA network in CRC, we analyzed the mRNA Seq, miRNA Seq data and clinical information from TCGA database. LncRNA, miRNA and mRNA signatures, were identified to construct risk score as independent indicators of the prognostic value in CRC patients. A composite clinicopathologic-genomic nomogram was developed to predict the overall survival (OS). 161 CRC specific lncRNAs, 97 miRNAs, and 161 mRNAs were identified to construct the ceRNA network. Multivariate Cox proportional hazards regression analysis indicated that nine-lncRNA, eight-miRNA, and five-mRNA signatures showed a significant prognostic value for CRC. Furthermore, a clinicopathologic-genomic nomogram was constructed in the primary cohort, which performed well in both the primary and validation sets. This study presents a nomogram that incorporates the CRC specific ceRNA expression profile, clinical features, and pathological factors, which demonstrate its excellent differentiation and risk stratification in predicting OS in CRC patients.